Characterization of the Universal Flavor in Chinese Butter Hotpot by Multiple Mass Spectrometry Detection Technology - Menglu Yang; Yuan Mei; Haimei Lai; Yali Wang; Yuli Huang; Xueqing Zeng; Lihong Ge; Nan Zhao (Journal of Food Quality)
Hotpot provides a multilevel unique flavor experience and is preferred by consumers who value various taste preferences. In the present study, results showed that alcohols, phenols, hydrocarbons, and others were the commonly predominant volatiles in all butter hotpot samples (74.43%∼92.92%). However, there were merely 25 codetected compounds determined among a total of 318 aroma compounds because of the discrepant ingredients and processing technique of hotpot samples, which were sampled from several representative manufacturers. Therefore, for the first time, multiple GC-Q-TOF/MS and GC-Orbitrap-MS methods were performed to explore the more 44 potential aroma compounds of butter hotpot, in which alpha-terpinyl, acetate, nonanal, piperitone, and (E)-lignstilde could further cause the differences in flavor intensity of spices aroma, smell of grease, and roasted, charred, and nutty (p<0.05). Linalool and nerol were the critical flavor precursors associated with ingredients and processing technic. Therefore, these results provide guidance for improving the butter hotpot formula and process technique.